Extension implementation of ILCA interventions: Dry-season cow supplementation and fodder banks - Taylor-Powell, E.; Suleiman, H. (International Livestock Centre for Africa, 1986)
Presents results of monitoring extent & rate of adoption of two government promoted ILCA intervention packages, dry season cow supplementation & fodder banks, amongs Fulani pastoralists in the two case study areas of Kurmin Birri & Abet in Subhumid Nigeria as well as adherence to the original design & modifications introduced, success of interventions in their stated goals, its persistence, side-effects and problems that arose in implementation.